Survival Motor Neuron (SMN) Protein Insufficiency Exacerbates Renal Ischemia/Reperfusion Injury - Qian, Xiaoqian; Du, Yichao; Jiang, Gengru; Lin, Fujun; Yao, Lei (Frontiers in Physiology, 2019)
The survival of motor neuron (SMN) protein is ubiquitously involved in spliceosome assembly and ribonucleoprotein biogenesis. SMN protein is expressed in kidney and can affect cell death processes. However, the role of SMN in acute kidney injury is largely unknown. In the current study, we found that the expression of SMN in the kidney was significantly reduced in both clinical ischemic acute kidney injury (AKI) and a mouse model of renal ischemia-reperfusion injury (IRI). We then used SMN heterozygous knockout (SMN+/-) mice and found that the declines in renal function, tubular injury, and tubular cell apoptosis after experimental IRI were significantly more severe in SMN+/- mice than those in their wild-type littermates. Concomitantly, the canonical transcription factor nuclear factor-κb (NFκb) signaling was enhanced in ischemic SMN+/- mice. In vitro, cobalt dichloride (CoCl2) treatment reduced SMN expression in proximal tubular epithelial cells. In addition, CoCl2-induced apoptosis and activation of NFκb signaling pathway were enhanced by transient transfection of a small-interfering RNA (siRNA) against SMN while attenuated by transient transfection of a full-length SMN plasmid. Taken together, this study for the first time supported the protective role of SMN in ischemic AKI.